In-Mouth Wine Aroma Analysis. - Perez-Jimenez, Maria (2024)
In-mouth aroma analysis under wine-tasting conditions is a challenging task. By combining the use of analytical tools such as solid phase micro-extraction (SPME) or stir bar sorptive extraction (SBSE) with the design of different devices and/or methodological approaches, it is possible to monitor the aroma release in the mouth at different times while simulating the consumption of wine. Two recently employed techniques to monitor in-mouth aroma release from wine are intra-oral SPME and in-mouth headspace sorptive extraction (HSSE). These procedures consist in the intra-oral extraction of wine volatiles into adsorbent/absorbent polymers after the oral exposure to the wine by using an SPME fiber or a stir bar also called a twister. Then, aroma compounds contained in both types of polymers are desorbed and analyzed by gas chromatography-mass spectrometry (GC-MS). Using these tools, the total amount of aroma released by each odorant can be determined. Through this, it is possible to compare the intra-oral amounts and release patterns of different types of wine volatiles, which can be useful for determining their oral aroma persistence. This chapter provides a step-by-step guideline for the extraction, desorption, and analysis by GC-MS of the wine aroma compounds released in the mouth after wine tasting by using intra-oral SPME or in-mouth HSSE procedures.